Optimizing board structure for ESG integrity: Nonlinear size effects and diversity moderation on greenwashing - Jingzhuo Yu; Yong-Sik Hwang (PLoS ONE, 2026)
This study examines the nonlinear relationship between board size and Environmental, Social, and Governance (ESG) greenwashing and explores how board diversity moderates this association. Using panel data from Chinese A-share listed firms between 2009 and 2023, we employ quadratic fixed-effects regression models to test for an inverted U-shaped relationship. The results indicate that medium-sized boards (10–13 directors) exhibit the highest propensity for greenwashing. Further analyses reveal heterogeneous moderating effects across four dimensions of board diversity—gender, functional background, nationality, and age. Specifically, reaching a critical mass of at least two female directors or increasing functional diversity strengthens the inverted U-shaped relationship, whereas greater age or nationality diversity attenuates it. Drawing on fraud triangle theory, this study uncovers a previously overlooked nonlinear mechanism underlying board size and ESG greenwashing. Moreover, it identifies two distinct diversity-driven pathways: resource-based mechanisms (gender and functional diversity) and supervision-based mechanisms (nationality diversity). These findings extend existing literature on board governance and greenwashing and provide practical insights, suggesting that firms should avoid the “danger zone” associated with medium-sized boards and adopt targeted diversity strategies to mitigate ESG greenwashing risks.